2019
DOI: 10.3390/ani9050198
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Abandonment of Surgical Castration in Pigs: How is Immunocastration Perceived by Italian Consumers?

Abstract: Immunocastration of pigs represents an alternative method to surgical castration, being more respectful of animal welfare. However, this new technology may not be accepted by consumers due to their perception of possible risks tied to the use of the product, thus representing a concern for the production sector. The study aimed at verifying the attitude of Italian consumers towards immunocastration and to assess whether their perception can be affected by science-based information on advantages and disadvantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Low awareness of pig castration issues, identified in both surveys, has also been reported in a previous study in Brazil [ 33 ] and in several European countries [ 4 , 30 , 31 , 32 , 47 , 55 , 56 , 58 ]. We also identified low awareness of tail docking, adding to previous studies that found that Brazilians have low awareness of animal production practices in general [ 33 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Low awareness of pig castration issues, identified in both surveys, has also been reported in a previous study in Brazil [ 33 ] and in several European countries [ 4 , 30 , 31 , 32 , 47 , 55 , 56 , 58 ]. We also identified low awareness of tail docking, adding to previous studies that found that Brazilians have low awareness of animal production practices in general [ 33 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 78%
“…As shown in this study, Jansen et al [ 53 ] found that some people have negative attitudes towards chemicals in food and consider them unnatural and detrimental to health, and associate “chemical” with danger. Concern that immunocastration (and to a lesser extent, pain medications) would leave residues in the meat was also reported by participants, as shown by others [ 47 , 54 , 55 ]. This was a reason stated by a few participants to support surgical castration without pain control.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, the results of consumer studies are unequivocal. A recent study by Di Pasquale and co-authors [121] shows that Italian consumers rate meat from immunocastrates more positively than meat from surgical castrates or entire males, with a low risk perception of immunocastration. This leads to a higher willingness to pay for products from immunocastrated male pigs.…”
Section: Societal Concerns and Immunocastrationmentioning
confidence: 97%
“…Immunocastration creates specific antibodies that recognize and bond to the hormone GnRH-I, preventing bonding with pituitary receptors, thus inhibiting FSH and LH secretion, causing infertility [10,12]. Thus, immunocastration has proven inhibition of reproductive activity in pigs [13][14][15], cattle [16,17], horses [18], sheep [19], mice [20][21][22][23], camelids [24], cats [25], chickens [26], and dogs [9,27,28]. Bansal and collaborators (2019) have recently developed and proven that immunogenicity of a vaccine able to develop immunity against GnRH and rabies virus simultaneously in mice [29].…”
Section: Introductionmentioning
confidence: 99%